Utilization of Sargassum sp. to Improve Blood Plasma Minerals for Thin Tailed Weaning Ram - Paga, Agustinus; Agus, Ali; Kustantinah, Kustantinah; Bulu, Petrus Malo; Tavares, Luis (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
This study aimed to study the blood plasma minerals of thin-tailed weaning ram prior to administration of Sargassum sp. as a source of minerals. Research materials and methods. The use of Sargassum sp. seaweed flour. sun-drying on 16 weaned thin tailed rams, aged 5-6 months with a bodyweight of ±11.8 kg for 3 months, using a 4x4 completely randomized design (CRD) with four treatments, namely T1 = forage + concentrate + 0% minerals of concentrate, T2 = Forage + concentrate + cow booster minerals 0.38% of concentrate, T3 = forage + concentrate + Sargassum sp.5% of concentrate, T4 = forage + concentrate + Sargassum sp.10% of concentrate. The observed research variables were the consumption of macro minerals (Ca, Mg, K, and Na and micro minerals Cu, Fe, and Zn) and balance of macro minerals Ca, Mg, K. and Na and micro minerals (Cu, Fe, and Zn blood plasma before and after treatment with seaweed Sargassum sp. The results showed that the treatment had a significant effect (P<0.05) on mineral Ca consumption, Mg, K, Na, Cu, Fe, and Zn. Blood plasma minerals before treatment did not differ on Mg, Na, Cu, Fe, Zn, but had a significant effect (P<0.05) on Ca and K. The treatment had a significant effect (P<0.05) on minerals Mg, Cu, and Fe in blood plasma, but did not affect Ca, K, Na, Zn. Based on the results obtained, the use of Sargassum sp. 10% of the total concentrate with sun drying can increase the consumption of macro and micro minerals as well as increase the minerals Mg, Cu, and Fe in the blood plasma of weaning rams.